Predictive value of volumetric parameters based on 18F-PSMA-1007 PET/CT for prostate cancer metastasis - Li, Yanmei; Chen, Jian; Wang, Xiaojuan; Yang, Pengfei; Yang, Jiqin; Zhao, Qian; Li, Juan (Frontiers in Oncology, 2024)
Purpose of the Report: To explore the value of 18F-labeled prostate-specific membrane antigen (PSMA-1007) positron emission tomography (PET)/computed tomography (CT), the maximum standardized uptake value (SUVmax) of the primary tumor, prostate PSMA-tumor volume (PSMA-TVp), and prostate total lesion PSMA (TL-PSMAp) for predicting prostate cancer (PCa) metastasis and follow-up evaluation in primary PCa lesions. Materials and Methods: 18F-PSMA-1007 PET/CT data of 110 consecutive newly diagnosed PCa patients were retrospectively analyzed. Patients were divided into non-metastatic, oligometastatic, and extensive metastatic groups. The predictive power was assessed using the receiver operating characteristic curve. Multi-group one-way analysis of variance and post-hoc tests were used to compare the groups. Patients were monitored post-therapy to evaluate treatment effectiveness. Results: Among the 110 patients, 66.4% (73) had metastasis (29 oligometastatic, 44 extensive metastasis). AUCs for Gleason score (GS), total prostate-specific antigen(TPSA), SUVmax, TL-PSMAp, and PSMA-TVp were 0.851, 0.916, 0.834, 0.938, and 0.923, respectively. GS, TPSA, SUVmax, TL-PSMAp, and PSMA-TVp were significantly different among the groups. In the post-hoc tests, differences in GS, TPSA, SUVmax, TL-PSMAp, and PSMA-TVp between the non-metastatic and oligometastatic groups and non-metastatic and extensive metastatic groups were significant (P<0.010). Differences in TL-PSMAp and PSMA-TVp between oligometastatic and extensive metastatic groups were significant (P=0.039 and 0.015, respectively), while those among GS, TPSA, and SUVmax were not. TL-PSMAp and PSMA-TVp distinguished between oligometastatic and extensive metastases, but GS, TPSA, and SUVmax did not. In individuals with oligometastasis, the implementation of active treatment for both primary and metastatic lesions may result in a more favorable prognosis. Conclusions: 18F-PSMA-1007 PET/CT volumetric parameters PSMA-TVp and TL-PSMAp can predict PCa oligometastasis.